A validated HPLC method for estimation of Gymnemic acids as Deacyl gymnemic acid in various extracts and formulations of Gymnema sylvestre - Kusum Devi; Nimsha Jain (International Journal of Phytomedicine, 2014)
The aim of present study is to develop and validate a simple, precise and rapid HPLC method for the quantification of gymnemic acid as Deacyl gymnemic acid in Gymnema sylvestre extracts and formulations. The analysis was performed by reverse-phase chromatography on a phenomenex C18 column with isocratic elution of acetonitrile: buffer (23:77 v/v) at a flow rate of 2.0mL/min. The method was validated in terms of precision, specificity, selectivity, linearity, limit of quantitation and detection, accuracy, recovery, and stability as per the ICH guidelines. The linear range of method was found to be 50- 800μg/ml with correlation coefficient of 0.9998. The developed method was found to be a relatively simple, precise and reproducible for the quantification of gymnemic acids in gymnema sylvestre extracts and formulations.